2017
DOI: 10.5296/emsd.v6i1.10931
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Likelihood of Adoption of Green Practices in Hotels: The Case of Abuja and Lagos, Nigeria

Abstract: Despite the high level of awareness of sustainable practices around the globe, and literatures on its adoption in businesses, studies showed very few studies are conducted in less advanced countries like Nigeria. Given the rising consumption of resources, apprehension for the environs and sudden realization among people for practices that are friendlier, the trend is gradually picking up in the Nigerian hotel industry. The hotel is facing challenges accepting green practices due to little information on green … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
(52 reference statements)
1
9
0
Order By: Relevance
“…SMEs face less pressure to enhance their environmental performance, which may be the reason for the low significant effect of customer pressure on the intention to adopt EMPs. The findings of the current study were similar to earlier studies done by Anton et al (2004), Hsu et al (2013), andMuazu et al (2017).…”
Section: H2csupporting
confidence: 93%
See 2 more Smart Citations
“…SMEs face less pressure to enhance their environmental performance, which may be the reason for the low significant effect of customer pressure on the intention to adopt EMPs. The findings of the current study were similar to earlier studies done by Anton et al (2004), Hsu et al (2013), andMuazu et al (2017).…”
Section: H2csupporting
confidence: 93%
“…Anton et al (2004) found that pressure from customers, investors, and the public has driven the adoption of environmental practices. Studies by Hsu et al (2013) and Muazu et al (2017) also discovered a significant association between customer pressure and green practice adoption. They confirmed that customer pressure is the primary determinant for adoption.…”
Section: Customer Pressurementioning
confidence: 94%
See 1 more Smart Citation
“…The industry is facing challenges accepting green practices due to insufficient information on sustainability and its advantages, government incompetence to impose guidelines on environmental health, and absence of highlighting the importance of green practice. Going green drives businesses to improve know-hows and execute groundbreaking ideas to protect the environment and improve business performance [34]. [35] discovered the industry is yet to understand the UNSDGs prevailing conditions for business undertakings in improving community wellbeing.…”
Section: Hospitality Industrymentioning
confidence: 99%
“…In the context of Nigeria like other countries across the globe, the hospitality industry is among the strategic sector for job creation (Adedipe & Adeleke, 2016; Adeola & Ezenwafor, 2016). However, while the implementation of environmental management friendly practices in the manufacturing sector has been on for long, focus on the hospitality industry is somewhat a new phenomenon, especially in developing countries like Nigeria (Mu’azu et al, 2014). The increase in hotel development in Nigeria calls for more environmentally friendly practices (Mu’azu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%